Análise antropotecnológica do desenvolvimento de novos produtos na produção artesanal : caso das rendeiras de bilro da Vila de Ponta Negra em Natal, RN - Barros, Kleber da Silva (2009)
Brazilian craft production plays an important role in the generation of employment and income for many families in every state across Brazil. In Natal, Rio Grande do Norte, Brazil, among many types found, identifies itself with the production of bobbin-lace, still practiced in Ponta Negra Village for ancient craftswomens of city that try to preserve the art and tradition of bobbin-lace. This work presents the results of an analysis conducted based in concepts of anthropotechnology, on the effects of a design workshop held with bobbin-lace craftswomen in the village of Ponta Negra in July of 2006. The workshop was intended to propose a new concept of products and a new alternative for production in the activity of the craftswomen, on the premise that the laces could be used as a detail inserted into other industrial products such as shirts, bags, towels, etc. Evaluations after the workshop showed that none of the artisans continued to work, indicating that actions focused solely on products did not generate representative results in the production of bobbin-lace. Evaluations also indicated that knowledge about the artisan's personal and professional characteristics, organization, pace, workload, and cultural and historical issues that permeate the activity are essential to the success of technology transfer, particularly when the transfer affects the craft production as it relates to the inseparable aspects of the craftswomen's work and lifestyle